Horan, Sharon. Interview. Sharon talks about her career as an occupational therapist in Newfoundland and Labrador 1987-2022 - Manojlovich, Mary (2022)
Interview with Sharon Horan about her career as an occupational therapist in St. John's from graduation in 1987 to present day;how she chose occupational therapy as a career;attended school of Occupational Therapy at Dalhousie with other Newfoundland students on bursary; first job as an OT at St. Clare's; events leading up to establishing one of the first private practices in Newfoundland in 1994; evolution of Sharon's private practice over 28 years; core values and principles; experience as chair of Newfoundland and Labrador Occupational Therapy Board.